SARS-CoV-2 Infections among Vaccinated Patients on Maintenance Dialysis, January 1–August 31, 2021, United States. Issue 11 (24th November 2022) - Bardossy, Ana Cecilia; Angeles, Jesenia; Booth, Stephanie; Fike, Lucy; Wadley, Ashley; Rha, Brian; Lacson, Eduardo; Manley, Harold J.; Johnson, Doug; Apata, Ibironke W.; Novosad, Shannon
Key Points: Dialysis facilities voluntarily reported severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections in vaccinated dialysis patients detected between January 1, 2021, and August 31, 2021, to the Centers for Disease Control and Prevention. Among 4087 patients reported, most were symptomatic, a third required hospitalization, and 9% died within 30 days of diagnosis. Monitoring SARS-CoV-2 infections and outcomes among vaccinated people on dialysis provides valuable insight into this population.